STRATEGI PENINGKATAN EKSPOR UMKM INDONESIA SELAMA PANDEMI COVID-19 (Media Mahardhika, 2021)
Exports play an important role in the economy of a country, including Indonesia. However, the value of Indonesia's exports, especially those from MSMEs, is still very low. This study aims to map a strategy to increase the export of Indonesian MSMEs and analyze these strategies based on behavioral theory in order to find out the right strategy to be implemented in the midst of the COVID-19 pandemic. This study uses a qualitative method that focuses on a bibliographic approach. The object of this research is 14 scientific articles that review the export of Indonesian MSMEs from 2009 to 2019. The results show that there are ten strategies that can be done to increase the export of Indonesian MSMEs, namely, training, increasing promotion, providing easy access to capital, implementing information technology and communication, infrastructure improvement, product standardization, product innovation enhancement, government policy support, MSME rating, and export procedure simplification. All of these strategies are related to the theory of behavior, namely the theory of planned behavior and the theory of attribution. The implementation of all these strategies can also be adapted to the conditions of the COVID-19 pandemic.